Dosimetric characteristics of 6 MV photons from TrueBeam STx medical linear accelerator: simulation and experimental data - N. D., Ton; B. D., Linh; Q.T., Pham (Nuclear Science and Technology, 2019)
A TrueBeam STx is one of the most technologically advanced linear accelerators for radiotherapy and radiosurgery. The Monte Carlo simulation widely used in many applications in various fields such as nuclear physics, astrophysics, particle physics, and medicine. The Geant4/GATE Monte Carlo toolkit is developed for the simulation in imaging diagnostics, nuclear medicine, radiotherapy, and radiation biology to more accurately predict beam radiation dosimetry. In this work, we present the simulation results of the dosimetric characteristics of a 6 MV photon beam of TrueBeam STx medical LINAC using Monte Carlo Geant4/GATE. The percentage depth dose (PDD), central axis depth dose (Profile) have been simulated and compared with those measured in a water phantom for field sizes 10×10 cm2 via the gamma-index method. These results will permit to check calculation data given by the treatment planning system.